1574. Cancer Chemotherapy May Induce Acquisition of Antibiotic Resistance Genes in Antibiotic-Naïve Cancer Patients. (26th November 2018) - Apewokin, Senu; Andersen, Heidi M; Medlin, Stephen; Mersha, Tesfaye; Weiss, Alison; Haslam, David; Davies, Stella M
Abstract: Background: The human gut serves as a critical reservoir for bacteria and plasmids that encode antibiotic resistance genes (ARGs). Antibiotic exposure contributes to the acquisition of such ARGs; consequently efforts to curtail development of antibiotic resistance focus on minimizing exposure through antibiotic stewardship programs. Cancer chemotherapy (CC) drugs often possess potent antimicrobial properties; however, their contribution to the development of gut ARGs has not been well documented. We sought to evaluate the contribution of CC agents to the development of gut microbial ARGs using metagenomic sequencing. Methods: We collected stool samples pre- and post-initiation of chemotherapy in antibiotic-naïve patients receiving antineoplastic agents for cancer treatment. Antineoplastic agents included fludarabine, busulfan, cyclophosphomide, mesna and melphalan for induction chemotherapy or conditioning during stem cell transplantation. We performed metagenomic shotgun sequencing on these samples and compared the relative abundance of ARGs pre- and post- treatment initiation. Three thousand and twenty-one ARGs were categorized into 15 functional pharmaceutical classes (by agents used for patient care or environmental cleaning). For group comparisons t -test and/or two-way ANOVA was performed. Results: Seven patients provided pre- and post samples. Overall there was a trend toward reduction/eradication of ARGs in 10 of 15 of antibiotic resistance gene classes. For the rifampin class no ARGs were noted in either pre- or post-samples. For four of the ARG classes (aminoglycoside, β-lactamase, fosfomycin, multidrug efflux pumps), there was an acquisition or trend toward an increase in ARG abundance. Conclusion: Cancer chemotherapy agents may be contributory to the acquisition of aminoglycoside, β-lactamase, fosfomycin, multi-drug efflux pump resistance genes in cancer patients. Of note, these genes confer resistance to some of the most important therapeutic or environment cleaning compounds utilized during clinical care. Further studies are warranted and ongoing to confirm these findings and overcome sample size limitations. Disclosures: S. Apewokin, Viracor: Assay provision for research by viracor, Research support